A Cross-Country Comparison of Operational Efficiency between Chinese and Pakistani Commercial Banking Industries - Zhu, Nan; Shah, Wasi Ul Hassan (International Journal of Operational Research/Nepal, 2019)
The objective of this paper is to make a cross-country comparative analysis on operational efficiency (OE), that is consisted of technical efficiency (TE), pure technical efficiency (PTE), and scale efficiency (SE), between the industries of Chinese and Pakistani commercial banks (CBs) for the year 2012 to 2016. To measure the OE score of a CB, we apply a non-parametric approach known as data envelopment analysis (DEA) method. From the previous studies on CBs, we adopt two models, i.e. Model A and Model B, with a different set of inputs and outputs variables to assess that does efficiency scores vary with change in a number of inputs and outputs. The empirical analysis finds that both Mean TE and PTE scores of Chinese CBs are always relatively higher than the corresponding scores of Pakistani CBs in the time period 2012-2016. However, Mean SE score of Chinese CBs obtained by using Model A is relatively lower than of Pakistani counterparts. It also finds that the Mann-Whitney U test shows that there is a significant difference between Mean TE scores of CBs in the commercial banking industries of both countries for the years 2012-2016.